058 Tolosa-Hunt syndrome with features of trigeminal autonomic cephalagia, pituitary enlargement, and non-lateralised headache. Issue 6 (27th May 2022) - Sim, Nicholas Keyi; Liew, Sze Yii; Warren, Daniel; Hassan, Ahamad
Abstract : We present a case of Tolosa-Hunt syndrome with a headache phenotype mimicking a right-sided trigemi- nal autonomic cephalagia (hemicrania continua), and serial MRI imaging showing a stable enlarged pituitary. She was diagnosed initially with common migraine, revised to hemicrania continua, then chronic daily headache, before finally arriving at her diagnosis. She tried multiple anti-migraine therapies and her best response was to indomethacin, discontinued due to gastrointestinal side effects. Her diagnosis was achieved after her headache changed to a left sided headache with a left sided cavernous sinus syndrome, 4 years into her disease course, despite her serial surveillance scans. She responded well to steroids. This case demonstrates Tolosa-Hunt syndrome may not be side-locked, and the need to consider inflam- matory causes of headache when faced with a patient with persistent headaches and 'incidental' pituitary adenoma. nchlasim@doctors.org.uk 54